2011
DOI: 10.1667/rr2297.1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Lipidomics of γ-Radiation-Induced Lung Injury: Mass Spectrometric Characterization of Cardiolipin and Phosphatidylserine Peroxidation

Abstract: Oxidative damage plays a significant role in the pathogenesis of γ-radiation-induced lung injury. Endothelium is a preferred target for early radiation-induced damage and apoptosis. Given the newly discovered role of oxidized phospholipids in apoptotic signaling, we performed oxidative lipidomics analysis of phospholipids in irradiated mouse lungs and cultured mouse lung endothelial cells. C57BL/6NHsd female mice were subjected to total-body irradiation (10 Gy, 15 Gy) and euthanized 24 h thereafter. Mouse lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 65 publications
3
69
1
1
Order By: Relevance
“…Figure 4 shows the MS/MS spectrum of the ion at m/z 697.8, which analysis and interpretation allowed the assignment of this ion as the short chain oxidation product CL- The CL hydroperoxy and hydroxy derivatives were already observed in CL oxidation in in vitro and in vivo studies (Tyurin et al, 2000, Tyurina et al, 2011. In this study, we have identified hydroxy and hydroperoxy -CL species at m/z 761.7 and 773.6 (Table 2).…”
Section: Effects Of Chronic Stress In Lipid Profiling Of Brainmentioning
confidence: 55%
“…Figure 4 shows the MS/MS spectrum of the ion at m/z 697.8, which analysis and interpretation allowed the assignment of this ion as the short chain oxidation product CL- The CL hydroperoxy and hydroxy derivatives were already observed in CL oxidation in in vitro and in vivo studies (Tyurin et al, 2000, Tyurina et al, 2011. In this study, we have identified hydroxy and hydroperoxy -CL species at m/z 761.7 and 773.6 (Table 2).…”
Section: Effects Of Chronic Stress In Lipid Profiling Of Brainmentioning
confidence: 55%
“…Primary Endothelial Cell Culture-Mouse primary endothelial cells were isolated from pulmonary tissue (n ϭ 12 mice/ genotype) as described previously (22). Cells were cultured on a collagen matrix in 2% O 2 , 5% CO 2 , 93% N 2 in a Coy hypoxic glove box/chamber (Coy Laboratories, Inc.) in Opti-MEM (Invitrogen), 10% FBS, 2 mM glutamine, 0.2% retinal derived growth factor (ENDOGRO; Vec Technologies), 10 units/ml heparin, 0.1 mM nonessential amino acid supplement (Invitrogen), and 55 M ␤-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
“…(b) Unigram frequencies of observed oxidized acyl chains upon apoptosis induction by different stimuli highlight mono-oxygenated C18:2 CL species. A, NAO-light (current work); B, actinomycin D (2012); 61 C, actinomycin D (2014); 19 D, controlled cortical impact; 19 E, gamma irradiation (2008); 22 F, gamma irradiation (2009); 57 G, gamma irradiation (2011, in vitro ); 22 H, gamma irradiation (2011, in vivo ); 22 I, hyperoxia; 60 J, mechanical injury; 58 K, actinomycin D (current work); L, rotenone (2013); 56 M, rotenone (2015); 62 N, staurosporine; 65 O, single walled carbon nanotubes; 63 and P, whole body radiation. 19 In the inset boxplot, the same frequencies are shown by grouping the stimuli as follows: NAO-light (this work) in red, in vitro (B, C, F, G, J, K, L, and N) in blue, and in vivo (D, E, H, I, M, O, and P) in green.…”
Section: Figurementioning
confidence: 99%